Data House: Digitalization Profile and Dynamics Population Wonorejo with Website Development for Support Becoming a Smart Village - Izzalqurny, Tomy Rizky; Yanto, Alif Faruqi Febri; Ferdiansyah, Rifaldy Adinandra (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This project aims to develop and implement a web-based information system in Wonorejo Village to address inefficiencies in administrative processes and limitations in digital access for both village officials and the community. The research explores the importance of digital transformation in village administration and its potential to improve public services. Method: A participatory approach was used, including direct observation and Focus Group Discussions (FGD) with village officials. Website development was carried out to support administrative functions, followed by training sessions for the village officials. Data was collected through pre- and post-training surveys to measure improvements in efficiency and digital literacy. Practical Application: The results of the community service show that implementing the website increased administrative efficiency, reduced service time, and expanded access to information for the public. Conclusion: The web-based information system successfully improved administrative efficiency and enhanced the digital literacy of village officials. These findings reinforce the role of technology in strengthening village governance and demonstrate potential for replication in other rural areas.